IMPLEMENTASI WEB SERVICE DENGAN METODE REST API UNTUK INTEGRASI DATA COVID 19 DI SULAWESI SELATAN - Baharuddin, Baharuddin; Wakkang, Hamka; Irianto, Bambang (Fakultas Teknik Universitas Muhammadiyah Parepare, 2022)
Web service is a software that is used as a liaison that allows various systems to communicate with each other without being affected by differences in platforms and not directly connected to the database they have. So the web service will provide existing services on the old system to be able to communicate with the new system without making changes to both. This paper will explain about making web services that can integrate web applications and mobile applications in the COVID-19 Development Information System in South Sulawesi. Using RESTful technology to exchange data in the form of JSON via URI (Uniform Resource Identifier). In this study, the author can produce a centralizedby utilizing websiteweb service the REST APImethod in the data retrieval process which aims to combine or unify the data even though it comes from different databases.